Dilthey dossier Studies - Kahlmeyer-Mertens, Roberto Saraiva; Kisse, Eduardo Henrique Silveira (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2019)
By publishing its third edition, the Aoristo – International Journal of Phenomenology, Hermeneutics and Metaphysics reaffirms its commitment to contribute to the dissemination of scientific knowledge and to the growth of phenomenological philosophy, hermeneutical philosophy and metaphysics at the Universidade Estadual do Oeste do Paraná – Unioeste, as well as in a modest way in the Brazilian and international philosophical scene. As affirmed in its editorial project, this journal reinforces its purpose of being a welcoming space to both national and international partners. The objective is to bring together institutions and researchers that not only promote the mutual strengthening of academical bonds but also the incitement and the consolidation of a research ambience propitious to the internationalization and the qualification of the intellectual production within the aforementioned thematic fields.